2021
DOI: 10.1136/bmjgast-2021-000705
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early cholecystectomy on the readmission rate in patients with acute gallstone cholangitis: a retrospective single-centre study

Abstract: Background and aimsThe pathogenesis of acute cholangitis (AC) occurs with biliary obstruction followed by bacterial growth in the bile duct. The leading cause of AC is obstructing gallstones. There have been conflicting theories about the optimal timing for cholecystectomy following AC. The aim of this study is to assess the impact of early cholecystectomy on the 30-day readmission rate, 30-day mortality, 90-day readmission rate and the length of hospital stay.MethodsThis retrospective study was performed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Cholecystectomy, either early or delayed, thus remains the best protector against RBE [ 29 , 30 , 51 ], approaching 90% of protection [ 7 ]. In addition, reviews showed that RBE is definitively lower if cholecystectomy is carried out early vs delayed (2–10% vs 24–47%) [ 13 , 15 , 29 31 ]. While a better reduction in the risk of RBE is achieved the sooner cholecystectomy is carried out [ 12 , 42 , 52 ], the definition of “early” cholecystectomy after endoscopic treatment of choledocholithiasis remains variable [ 1 , 28 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cholecystectomy, either early or delayed, thus remains the best protector against RBE [ 29 , 30 , 51 ], approaching 90% of protection [ 7 ]. In addition, reviews showed that RBE is definitively lower if cholecystectomy is carried out early vs delayed (2–10% vs 24–47%) [ 13 , 15 , 29 31 ]. While a better reduction in the risk of RBE is achieved the sooner cholecystectomy is carried out [ 12 , 42 , 52 ], the definition of “early” cholecystectomy after endoscopic treatment of choledocholithiasis remains variable [ 1 , 28 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, elderly and patients with higher comorbidity score are not significantly associated with an increased incidence of RBE (Table 1 ). Yet, index cholecystectomy after ERCP have been demonstrated to be secure, with fewer or at least no increased risk of complications [ 12 , 13 , 25 27 , 42 , 49 , 51 ], along with the prevention of RBE [ 3 , 7 , 16 , 20 , 21 , 29 31 , 43 , 44 , 49 51 ]. Age and comorbidity should not be an obstacle or a deterrent to proceed to early cholecystectomy or even at the index admission after the endoscopic removal of CBDS, except when risk is prohibitive [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations